MNAC 2004. - Mnac, Bukarest (Bucuresti : MNAC (Muzeul National de Arta Contemporana) Bucuresti, 2004)
Botea, Irina ; Büchel, Christoph ; Colomer, Jordi ; Comanescu, Nicolae ; Cosma, Stefan ; Croitoru, Alexandra ; Dabernig, Josef ; Dan, Calin ; Dan, Suzana ; Euroartist Bucuresti ; Gontz, Casa ; Gorzo ; Grigorescu, Ion ; Jacobi, Peter ; Kipphoff, Karen ; Kiraly, Josif ; Mihaltianu, Dan ; Motti, Gianni ; Nanca, Vlad ; Pogacean, Cristian ; Preda-Sanc, Marilena ; Puiu, Cristi ; SubREAL ; Vatamanu, Mona ; Tudor, Florin ; Achour, Boris ; Cantor, Mircea ; Dejanov, Plamen ; Geers, Kendell ; Lavier, Bertrand ; Scurti, Franck ; Bernea, Horia ; Neagu, Paul ; Büchel, Christoph ; Motti, Gianni
Engels en Roemeens
boek